Dynamic Variations in Brain Glycogen are Involved in Modulating Isoflurane Anesthesia in Mice - Ze Fan; Zhihao Zhang; Shiyi Zhao; Yuanyuan Zhu; Dong Guo; Bo Yang; Lixia Zhuo; Jiao Han; Rui Wang; Zongping Fang; Hailong Dong; Yan Li; et al. (Neuroscience Bulletin, 2020)
General anesthesia severely affects the metabolites in the brain. Glycogen, principally stored in astrocytes and providing the short-term delivery of substrates to neurons, has been implicated as an affected molecule. However, whether glycogen plays a pivotal role in modulating anesthesia–arousal remains unclear. Here, we demonstrated that isoflurane-anesthetized mice exhibited dynamic changes in the glycogen levels in various brain regions. Glycogen synthase (GS) and glycogen phosphorylase (GP), key enzymes of glycogen metabolism, showed increased activity after isoflurane exposure. Upon blocking glycogenolysis with 1,4-dideoxy-1,4-imino-D-arabinitol (DAB), a GP antagonist, we found a prolonged time of emergence from anesthesia and an enhanced δ frequency in the EEG (electroencephalogram). In addition, augmented expression of glycogenolysis genes in glycogen phosphorylase, brain (Pygb) knock-in (Pygb H11/H11 ) mice resulted in delayed induction of anesthesia, a shortened emergence time, and a lower ratio of EEG-δ. Our findings revealed a role of brain glycogen in regulating anesthesia–arousal, providing a potential target for modulating anesthesia.

Prefrontal Nectin3 Reduction Mediates Adolescent Stress-Induced Deficits of Social Memory, Spatial Working Memory, and Dendritic Structure in Mice - Hong-Li Wang; Ji-Tao Li; Han Wang; Ya-Xin Sun; Rui Liu; Xiao-Dong Wang; Yun-Ai Su; Tian-Mei Si (Neuroscience Bulletin, 2020)
Chronic stress may disrupt the normal neurodevelopmental trajectory of the adolescent brain (especially the prefrontal cortex) and contribute to the pathophysiology of stress-related mental illnesses, but the underlying molecular mechanisms remain unclear. Here, we investigated how synaptic cell adhesion molecules (e.g., nectin3) are involved in the effects of adolescent chronic stress on mouse medial prefrontal cortex (mPFC). Male C57BL/6N mice were subjected to chronic social instability stress from postnatal days 29 to 77. One week later, the mice exposed to chronic stress exhibited impaired social recognition and spatial working memory, simplified dendritic structure, and reduced spine density in the mPFC. Membrane localization of nectin3 was also altered, and was significantly correlated with behavioral performance. Furthermore, knocking down mPFC nectin3 expression by adeno-associated virus in adolescent mice reproduced the stress-induced changes in behavior and mPFC morphology. These results support the hypothesis that nectin3 is a potential mediator of the effects of adolescent chronic stress on prefrontal structural and functional abnormalities.

Bionic design in anti-bending and lightweight tube based on the tarsometatarsus of ostrich - Rui Zhang; Hao Pang; Dianlei Han; Shuliang Xue; Lei Jiang; Dong Li; Lige Wen; Jianqiao Li (Rendiconti Lincei. Scienze Fisiche e Naturali, 2020)